Brief Communication: On the magnitude and frequency of Khurdopin glacier surge events - D. J. Quincey; A. Luckman (The Cryosphere, 2014)
The return periods of Karakoram glacier surges are poorly quantified. Here, we present evidence of an historic surge of the Khurdopin Glacier that began in the mid-1970s and peaked in 1979. Measured surface displacements reached >5 km a−1, two orders of magnitude faster than during quiescence. The Khurdopin Glacier next surged in the late 1990s, equating to a return period of 20 years. Surge evolution in the two events shows remarkable similarity suggesting a common trigger. Surge activity in the Karakoram needs to be better understood if accurate mass balance assessments of Hindu-Kush–Karakoram–Himalaya glaciers are to be made.